Thermofluid-Acoustic Analysis of a Ranque-Hilsch Vortex Tube. (2016) - Wisnoe, Wirachman; Rahman, Khairil Muhaimin Abd; Istihat, Yusman; Natarajan, Valliyappan David
Abstract: This paper aims to present analysis of sound produced from a Ranque-Hilsch Vortex Tube. A microphone was used to record the sound produced close to the hot tube. It is observed that, for one configuration of RHVT, the sound produced contains a specific set of frequencies. When the inlet pressure is varied, these frequencies remain almost the same, however, the magnitude changes. The RHVT produces different set of frequencies when using different swirl generator. These sets of frequencies-magnitudes represent signatures for each configuration. Different swirl generator nozzles were tested and presented. Frequency signatures with their related thermofluid performance are obtained.